Herpes Simplex Mastitis: Case Report and Review of the Literature - Holly Brown; Paul Kneafsey; Amar Kureishi (Canadian Journal of Infectious Diseases)
The most common sites of herpes simplex virus (HSV) infection are around the oral cavity and the genitalia. However, HSV can infect any skin or mucous membrane surface. One uncommon site of HSV infection is the breast. Reports of herpetic breast infections are predominantly cases of transmission from a systemically HSV-infected neonate to the mother during breast-feeding. A review of the literature identified only six reports suggesting HSV breast lesions acquired by means other than through an infected infant. Of these, only one report suggests HSV transmission to the breast from a male sexual partner. A second case of clinically unsuspected symptomatic herpes mastitis presumably acquired from sexual contact in a 46-year-old woman is presented. Herpes simplex type 1 was isolated by using polymerase chain reaction and restriction fragment length polymerization techniques. The purpose of this report is to alert physicians to HSV mastitis.